2023
DOI: 10.1038/s41591-023-02566-3
|View full text |Cite|
|
Sign up to set email alerts
|

Microglia and complement mediate early corticostriatal synapse loss and cognitive dysfunction in Huntington’s disease

Daniel K. Wilton,
Kevin Mastro,
Molly D. Heller
et al.

Abstract: Huntington’s disease (HD) is a devastating monogenic neurodegenerative disease characterized by early, selective pathology in the basal ganglia despite the ubiquitous expression of mutant huntingtin. The molecular mechanisms underlying this region-specific neuronal degeneration and how these relate to the development of early cognitive phenotypes are poorly understood. Here we show that there is selective loss of synaptic connections between the cortex and striatum in postmortem tissue from patients with HD th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 198 publications
1
19
0
Order By: Relevance
“…To determine whether COX-2 levels might be elevated in neurodegenerative contexts, we decided to interrogate the zQ175 mouse model of Huntington’s disease. This mouse is thought to capture some of the earliest pathological events occurring in the presymptomatic phase of HD with synaptic dysfunction and the selective loss of corticostriatal synapses beginning at three months of agea time point that also coincides with the appearance of visual discrimination learning deficits . Both phenotypes have also recently been observed in presymptomatic HD patients. We initially performed immunoblotting using extracts from this mouse from a disease-affected brain region (striatum) and a region that is relatively spared (cerebellum).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether COX-2 levels might be elevated in neurodegenerative contexts, we decided to interrogate the zQ175 mouse model of Huntington’s disease. This mouse is thought to capture some of the earliest pathological events occurring in the presymptomatic phase of HD with synaptic dysfunction and the selective loss of corticostriatal synapses beginning at three months of agea time point that also coincides with the appearance of visual discrimination learning deficits . Both phenotypes have also recently been observed in presymptomatic HD patients. We initially performed immunoblotting using extracts from this mouse from a disease-affected brain region (striatum) and a region that is relatively spared (cerebellum).…”
Section: Resultsmentioning
confidence: 99%
“…Translation of [ 11 C]BRD1158, which is a highly specific, brain penetrant COX-2 PET radiotracer, and parallel studies characterizing the mechanism through which COX-2 influences synaptic pathology will (i) enable the study of COX-2 expression changes and distribution in the living brain to monitor and characterize key pathophysiological events in HD and potentially any microglial dynamics that might be important in synaptic elimination mechanisms; 55 (ii) allow for patient stratification in novel brain-permeable COX-2 inhibitor clinical trials; (iii) provide a therapeutic imaging biomarker for monitoring response to new treatment strategies; and (iv) generate a translatable tool to evaluate the role of COX-2 in HD and potentially other neurodegenerative diseases in the living human brain.…”
Section: Ligand Selection and Radiotracer Developmentmentioning
confidence: 99%
“…Although a role of the CP activation in normal brain development (Presumey et al, 2017;Schafer et al, 2012;Stephan et al, 2012;Stevens et al, 2007) and neurological diseases (Dalakas et al, 2020;Hong et al, 2016;Kjaeldgaard et al, 2018;Krance et al, 2021;Sekar et al, 2016;Shi et al, 2017;Watkins et al, 2016;Wilton et al, 2023;Yilmaz et al, 2021) have been widely reported, little is known about the LP and AP in the brain. Here, we provided transcriptional evidence arguing for an absence of the LP in the brain at steady state, another brain-specific aspect, based on the lack of expression LP serine proteases Masp1 and Masp2, and high-level expression of LP inhibitor, MAp44.…”
Section: Discussionmentioning
confidence: 99%
“…Cell type, temporal and spatial expression patterns of genes involved indicate non-redundant functions of the CP and AP. In addition, deficiency in Masp3-driven AP resulted in developmental and cognitive defects, indicating essential functions of the AP, an observation that highlights the necessity to disentangle differential involvement of the three complement activation pathways in development and diseases.Huntington's disease (Wilton et al, 2023), amyotrophic lateral sclerosis (ALS) (Kjaeldgaard et al, 2018), and multiple sclerosis (Watkins et al, 2016;Werneburg et al, 2020). However, unlike in the periphery, our understanding of the complement system in the brain remains incomplete.…”
mentioning
confidence: 99%
See 1 more Smart Citation